2020
DOI: 10.14309/ctg.0000000000000230
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Defecation Desire Between Patients With and Without Chronic Constipation: A Large-Scale Internet Survey

Abstract: INTRODUCTION: Defecation desire (DD) is an important physiological component of normal defecation. However, knowledge of DD in the general population and in individuals with chronic constipation (CC) is lacking. We aimed to assess the prevalence of DD in the general population and individuals with CC and to understand the impact of treatment on DD among individuals with CC. METHODS: We conducted an online questionnaire survey targeting the Japanese general population in 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 12 publications
(13 reference statements)
1
13
0
Order By: Relevance
“…The results of this study concur with previous reports in patients with constipation: Urge to defecate may be absent (14,21,22) or perceived as an abdominal sensation (14,22). The observations that in women with abnormal urge perception, viscerosensory referral area was larger (7,24,36), and a number of IBS-related symptoms (bloating, aching, cramping, colicky/griping, or sickness/nausea) were related to the urge to defecate, may suggest overlapping features with IBS with constipation (37,38).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study concur with previous reports in patients with constipation: Urge to defecate may be absent (14,21,22) or perceived as an abdominal sensation (14,22). The observations that in women with abnormal urge perception, viscerosensory referral area was larger (7,24,36), and a number of IBS-related symptoms (bloating, aching, cramping, colicky/griping, or sickness/nausea) were related to the urge to defecate, may suggest overlapping features with IBS with constipation (37,38).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies demonstrate that patients with functional constipation report an altered or absent perception of the urge to defecate or "call to stool" (14,(18)(19)(20)(21)(22). A recent Japanese population-based study (.20,000 participants) showed that 57.4% of 2,587 individuals who met the Rome IV criteria for functional constipation reported loss of defecation desire (21).…”
Section: Introductionmentioning
confidence: 99%
“…In total, seven studies stated that they used the Rome I criteria in 6 separate countries, [16][17][18][19]23,25,40 17 the Rome II criteria in 12 separate countries, [20][21][22][23][24][25][26][27][28][29][30][31]35,36,41,45 18 the Rome III criteria in 14 separate countries, [32][33][34]37,39,[42][43][44][46][47][48][49][50][51][52][53]55,58 and five the Rome IV criteria in 35 separate countries. 9,10,54,56,57 The pooled prevalence of FC, according to the criteria used to define its presence, is provided in Table 1. Pooled prevalence was highest when the Rome I criteria were used (15.3%; 95% CI 8.1% to 24.4%), and lowest when the Rome IV ...…”
Section: Prevalence Of Fc According To Criteria Used To Define Its Presencementioning
confidence: 99%
“…A web-based questionnaire-based survey reported that patients with CC had a significantly higher rate of LODD than healthy adults, with about 60% of patients losing their defaecation desire (DD), leading to the decrease of defaecation QOL. 22 Bile acids are expected to have a restorative effect on DD because they have an effect to lower the rectal sensory threshold, which is an objective index of DD. 23 24 EXB inhibits IBAT/ASBT (a transporter involved in bile acid reabsorption) in the terminal ileum.…”
Section: Discussionmentioning
confidence: 99%